2003
DOI: 10.1044/1058-0360(2003/092)
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Awareness and Phonemic Perception in 4-Year-Old Children With Delayed Expressive Phonology Skills

Abstract: The purpose of this study was to compare the phonological awareness abilities of 2 groups of 4-year-old children: one with normally developing speech and language skills and the other with moderately or severely delayed expressive phonological skills but age-appropriate receptive vocabulary skills. Each group received tests of articulation, receptive vocabulary, phonemic perception, early literacy, and phonological awareness skills. The groups were matched for receptive language skills, age, socioeconomic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
0
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 33 publications
10
87
0
17
Order By: Relevance
“…Phonological processing, in particular impairments related to phonological awareness (PA), is considered one of the core deficits characterizing dyslexia (Carroll & Snowling, 2004;Joanisse, Manis, Keating, & Seidenberg, 2000). PA refers to the explicit knowledge of the units that make up spoken words including syllables, onset and rime units and individual phonemes (Rvachew, Ohberg, Grawburg, & Heyding, 2003) and has been defined as the awareness of and access to the sound structure of one's oral language (Wagner & Torgesen, 1987). PA involves the awareness of the most basic speech units of a language, phonemes, as well as the larger units, such as rimes and syllables (Bird, Bishop, & Freeman, 1995;Rvachew et al, 2003;Stackhouse, Wells, Pascoe, & Rees, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Phonological processing, in particular impairments related to phonological awareness (PA), is considered one of the core deficits characterizing dyslexia (Carroll & Snowling, 2004;Joanisse, Manis, Keating, & Seidenberg, 2000). PA refers to the explicit knowledge of the units that make up spoken words including syllables, onset and rime units and individual phonemes (Rvachew, Ohberg, Grawburg, & Heyding, 2003) and has been defined as the awareness of and access to the sound structure of one's oral language (Wagner & Torgesen, 1987). PA involves the awareness of the most basic speech units of a language, phonemes, as well as the larger units, such as rimes and syllables (Bird, Bishop, & Freeman, 1995;Rvachew et al, 2003;Stackhouse, Wells, Pascoe, & Rees, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, the timing of remediation of the phonological speech sound disorder determined whether it would affect the development of the child's phonological awareness and reading development. Rvachew et al (2003) examined two groups of preschool children (4 years old)…”
Section: The Effects Of Speech-language Impairments On Literacy Develmentioning
confidence: 99%
“…Previous research has demonstrated that children with speech-language impairments are at an increased risk for the development of phonological awareness and reading disabilities (Larivee & Catts, 1999;Raitano et al, 2005;Rvachew et al, 2003).…”
Section: Phonemic Awareness Interventionsmentioning
confidence: 99%
See 2 more Smart Citations